Brain activation to briefly presented emotional words: Effects of stimulus awareness - Hoffmann, Marius (Hum Brain Mapp, 2014)
It is unknown to what extent briefly presented emotional words can be processed without awareness. By means of two independent functional magnetic resonance imaging studies, using either a block or an event‐related design, we investigated brain activation to very briefly presented threat related and neutral words during two backward masking conditions (with and without gap between target and mask). In both experiments, emotional words were perceived during the supraliminal “with gap” condition, but they were not recognized during the subliminal “without gap” condition, as indicated by signal detection theory analysis. Imaging results of both experiments showed increased activation of the amygdala, the medial prefrontal cortex and language‐processing cortical areas to negative versus neutral words during supraliminal but not subliminal conditions. These results suggest that even very briefly presented emotional words are capable of triggering increased cortical and subcortical processing; however, only when awareness of these stimuli is given. Hum Brain Mapp 36:655–665, 2015. © 2014 Wiley Periodicals, Inc.